Customer Relationship Management (CRM) Analysis of a Public Complaint Service Website at the Public Service Mall of South Lampung Regency - Chaniago, Firdaus; Putra, M. Natsir Hendy Tri; Oktaviani, Hafina; Winarti, Tri; Hasibuan, M. Said (Journal of Digital Literacy and Volunteering, 2025)
Public complaint service websites play an important role in supporting the improvement of digital-based public services, particularly within the Public Service Mall (PSM) environment that integrates multiple service institutions. Managing public complaints not only as administrative records but also as a means of managing relationships between government and citizens remains a key challenge in integrated public service delivery. This study aims to analyze Customer Relationship Management (CRM) on the Public Complaint Service Website of the Public Service Mall of South Lampung Regency.This research employed a qualitative approach using a case study method. Data were collected through system observation, interviews with service administrators, and document analysis. The data were analyzed descriptively using a CRM framework consisting of operational CRM, analytical CRM, and collaborative CRM dimensions. The results of the analysis indicate that operational CRM is the most prominent dimension, as reflected in the availability of a structured and well-documented complaint submission process. Meanwhile, analytical CRM and collaborative CRM have not been optimally utilized, particularly in terms of using complaint data for service performance evaluation and strengthening interactive follow-up communication mechanisms. The findings suggest that while the public complaint website has functioned effectively from an operational service perspective, further enhancement is required to enable the system to serve as a strategic instrument for improving the quality of digital public services.